The Value of a Twitter-based Community of Practice for Pharmacy Professionals in the UK - James Andrews (University of Minnesota Libraries Publishing, 2016)
As a means to work across settings and geography, @WePharmacists is a volunteer-led online social-media group open to anyone, with particular relevance to those operating in or with pharmacy teams in the UK. The goal of WePharmacists is to pursue better patient care and outcomes from medicines through shared learning and a connected pharmacy team. The core offering is facilitated tweet chats, on topics suggested by the community. Resources to aid members in connecting with others, finding information and using technology have been developed, along with materials to help members recognize the learning that occurs with social media use. Community members report the value of feeling part of a wider community, along with the benefit of learning from one another.   Type: Commentary